An Unusual MHC Molecule Generates Protective CD8+ T Cell Responses to Chronic Infection - Tsitsiklis, Alexandra; Bangs, Derek J.; Lutes, Lydia K.; Chan, Shiao W.; Geiger, Kristina M.; Modzelewski, Andrew J.; Labarta-Bajo, Lara; Wang, Yang; Zuniga, Elina I.; Dai, Shaodong; Robey, Ellen A. (Frontiers in Immunology, 2020)
The CD8+ T cell response to the intracellular parasite Toxoplasma gondii varies dramatically between mouse strains, resulting in stark differences in control of the parasite. Protection in BALB/c mice can be attributed to an unusually strong and protective MHC-1 Ld-restricted CD8+ T cell response directed against a peptide derived from the parasite antigen GRA6. The MHC-1 Ld molecule has limited peptide binding compared to conventional MHC molecules such as Kb or Db, which correlates with polymorphisms associated with “elite control” of HIV in humans. To investigate the link between the unusual MHC-1 molecule Ld and the generation of “elite controller” CD8+ T cell responses, we compared the GRA6-Ld specific T cell response to the well-studied OVA-Kb specific response, and demonstrated that GRA6-Ld specific T cells are significantly more protective and resistant to exhaustion in chronic T. gondii infection. To further investigate the connection between limited peptide presentation and robust T cell responses, we used CRISPR/Cas9 to generate mice with a point mutation (W97R) in the peptide-binding groove of Ld that results in broader peptide binding. We investigated the effect of this Ld W97R mutation on another robust Ld-restricted response against the IE1 peptide during Murine Cytomegalovirus (MCMV) infection. This mutation leads to an increase in exhaustion markers in the IE1-Ld specific CD8+ T cell response. Our results indicate that limited peptide binding by MHC-1 Ld correlates with the development of robust and protective CD8+ T cell responses that may avoid exhaustion during chronic infection.